2004
DOI: 10.1159/000079700
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Basic Fibroblast Growth Factor in Bladder Cancer Patients

Abstract: Introduction: Angiogenesis plays a significant role in the growth and progress of cancer, thus we evaluated the levels of urinary basic fibroblast growth factor (bFGF) in bladder cancer (Ca) patients and investigated any possible correlation between this angiogenic factor with tumor stage and grade. Materials and Methods: Urine samples from 41 patients with bladder Ca, 11 patients with history of bladder Ca but negative follow-up cystoscopy, 18 patients with benign prostate hyperplasia (BPH) and 15 normal heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Gravas et al [17] found elevated levels of urinary bFGF in patients with bladder cancer and its concentration seemed to be significantly related to the stage but not to the grade of the disease. Gupta et al [18] demonstrated that markedly elevated urinary bFGF may be useful as a noninvasive marker to assess progression of cystic renal development.…”
Section: Discussionmentioning
confidence: 98%
“…Gravas et al [17] found elevated levels of urinary bFGF in patients with bladder cancer and its concentration seemed to be significantly related to the stage but not to the grade of the disease. Gupta et al [18] demonstrated that markedly elevated urinary bFGF may be useful as a noninvasive marker to assess progression of cystic renal development.…”
Section: Discussionmentioning
confidence: 98%
“…Basic fibroblasts growth factor FGF, a member of the FGF family, is one of the most important angiogenic molecules stimulating endothelial cell proliferation, migration and differentiation to neovasculature. The implication of basic FGF in the biology of bladder cancer is confirmed and that the urinary basic FGF concentration seems to be significantly related to the stage has been demonstrated [9] .…”
Section: Introductionmentioning
confidence: 84%
“…The most common oncogenes and some of the tumor-suppressor genes relevant to BC are components of this pathway [85]. FGF2 protein levels have been reported to be significantly increased in BC tissues [82], [83], [86], [87], [88], and its expression is positively correlated with tumor grade [87]. FGF2 was also reported to be a predictor for recurrence when residual disease was present in the cystectomy specimen [79].…”
Section: Discussionmentioning
confidence: 99%